Boom, Bust and Up Again? Evolution, Drivers and Impact of Commodity Prices: Implications for Indonesia - World Bank (World Bank, Jakarta, 2013)
Indonesia is one of the largest commodity exporters in the world, and given its mineral potential and expected commodity price trends, it could and should expand its leading position. Commodities accounted for one fourth of Indonesia's Gross Domestic Product (GDP) and more than one fifth of total government revenue in 2007. The potential for further commodity growth is considerable. Indonesia is the largest producer of palm oil in the world (export earnings totaled almost US$9 billion in 2007 and employment 3.8 million full-time jobs) and the sector has good growth prospects. It is also one of the countries with the largest mining potential in view of its second-largest copper reserves and third-largest coal and nickel reserves in the world. This report consists of seven chapters. The first six chapters present an examination and an analysis of the factors driving increased commodity prices, price forecasts, economic impact of commodity price increases, effective price stabilization policies, and insights from Indonesia's past growth experience. The final chapter draws on the findings of the previous chapters and suggests a development strategy for Indonesia in the context of high commodity prices. This section summarizes the contents of the chapters and their main findings.